Inventory of taxonomic knowledge, as well as of regional diversity and endemism of Mexican species of Bursera (Burseraceae) - Rzedowski, Jerzy; Medina Lemos, Rosalinda; Calderón de Rzedowski, Graciela (Instituto de Ecología, A.C., 2005)
Our knowledge concerning the systematics of Bursera is still very imperfect. In this paper we present an annotated list of 82 Mexican species of this genus that merit at least a provisional recognition, indicating for every species its known geographical distribution on the state level. On the basis of this information a map and a table are presented showing the diversity of Bursera in the 32 Mexican administrative divisions. Fourty eight species are reported for Guerrero, 37 for Michoacán and Oaxaca, and 28 for Jalisco and Puebla. Tlaxcala has no recorded species, while Nuevo León, Tabasco and Quintana Roo shelter only one species each. A list of 33 Mexican species of Bursera with restricted distribution (40.3% of the total) is also presented, 10 being  reported only from the type locality and its surroundings, 10 additional ones known only from one state, and 13 extending their areas into two contiguous states. On the basis of these data six areas are defined and mapped, in which endemic species of the genus are known to concentrate.